Natural History of Anal Papillomavirus Infection in HIV-Negative Men Who Have Sex With Men Based on a Markov Model: A 5-Year Prospective Cohort Study - Zhang, Zewen; Ling, Xi; Liu, Lirong; Xi, Miaomiao; Zhang, Guozhen; Dai, Jianghong (Frontiers in Public Health, 2022)
Objective Men who have sex with men (MSM) are at increased risk for Human papillomavirus (HPV) infection compared to women and heterosexual men. We aimed to assess the incidence, clearance and duration of anal human papillomavirus (HPV) infection in HIV-negative MSM and the influencing factors in a 5-year prospective cohort study. Methods From April 2016 to April 2021, HIV-negative MSM were recruited and followed every 6 months in Urumqi, Xinjiang, China. Questionnaires and anal swabs were collected at baseline and every 6 months. We detected 37 anal HPV genotypes using the HPV Geno Array Diagnostic Kit Test. Incidence and clearance rates of anal HPV infection and the influencing factors were estimated using a two-state Markov model. Results A total of 585 MSM were included with a median age of 37 years [interquartile range (IQR): 31–43 years] and were followed for a median 2.8 years (IQR: 1.8–3.6 years). Incidence rates for any HPV and high-risk HPV (Hr-HPV) were 53.4 [95% confidence interval (CI): 49.1–58.0] and 39.0 (95% CI: 35.7–42.5)/1,000 person-months. Median duration of infection was 9.67 (95% CI: 8.67–10.86) and 8.51 (95% CI: 7.57–9.50) months, respectively. Clearance rates for any HPV and Hr-HPV were 50.9 (95% CI: 46.7–55.3) and 62.1 (95% CI: 56.8–66.7)/1,000 person-months, respectively. HPV16 and HPV6 had the highest incidence, lowest clearance rate and longest duration of infection among Hr-HPV and low-risk HPV (Lr-HPV) types, respectively. Receptive anal sex is a risk factor for any HPV [hazard ratio (HR) = 1.66, 95% CI: 1.16–2.38] and Hr-HPV infection (HR = 1.99, 95% CI:1.39–2.85). Recent anal sex without condom use was significantly associated with any HPV (HR = 1.80, 95% CI: 1.10–2.94) and Hr-HPV infection (HR = 2.60, 95% CI: 1.42–4.77). Age ≥35 years was significantly associated with Lr-HPV HPV infection only (HR = 1.40, 95% CI: 1.02–1.93). Both inserted and receptive anal sex (HR = 0.60, 95% CI: 0.40–0.89) and anal sex ≥2 times per week (HR = 0.61, 95% CI: 0.43–0.87) were associated with reduced Hr-HPV clearance. Six of the nine-valent vaccine types (HPV6, 11, 16, 18, 52 and 58) occurred most frequently, which indicates the need for high vaccination coverage in MSM. Conclusions In this cohort study, high incidence and low clearance of any HPV, Hr-HPV and individual HPV infections emphasize the importance of MSM vaccination. Modifiable behavioral factors such as condoms and drug use should be incorporated into HPV prevention strategies.